Pertumbuhan Penjualan, Proporsi Komisaris Independen, dan Tax Avoidance: Kajian Empiris Pada Perusahaan Consumer Non-Cyclical di BEI Tahun 2022-2024 - Jeanny Ann Samantha; Estralita Trisnawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study observes non-cyclical consumer companies listed on the Indonesia Stock Exchange from 2022 to 2024 to see how tax avoidance was affected by sales growth and the proportion of independent commissioners. Multiple linear regression analysis is the tool of choice in this quantitative study. A total of 132 observations were available for analysis from the 44 companies that made up the research samples selected through the purposive sampling process. The information was extracted from yearly financial audited reports and then processed with software EViews 13. The results of this study show that sales growth has a significant positive effect on tax avoidance. These results illustrate that increased sales encourage companies to reduce their tax expense so that profits appear to be in line with sales growth. Therefore, it can be concluded that when sales go up, tax avoidance practices also go up. Meanwhile, tax avoidance is not affected by proportion of independent commissioners. Limited access or authority prevents independent commissioners from controlling the company's taxation strategies and policies. It can be concluded that the proportion of independent commissioners who supervise has not been successful in minimizing tax avoidance.